Prestaciones de LTE sobre el canal aeronáutico - Martín-Vega, Francisco-Javier; Gómez, Gerardo; Mosquera, Carlos; Aguayo-Torres, María del Carmen (My University, 2014)
This work assesses the performance of Long Term Evolution (LTE) downlink over aeronautical channels associated to arrival, parking and en-route scenarios. The huge velocity related to some of these scenarios poses the following challenges: (1) (Inter-Carrier-Interference) ICI due to Doppler Shift, (2) ICI due to Doppler spread and (3) channel estimation errors. Taking into account these problems a physical layer LTE modem has been implemented. Results reveals that LTE can achive good performance in air-to-ground communications with aircraft moving at 1500 km/h without a complex receiver.
Keywords: Aeronáutica -- Sistemas de comunicaciones; Sistemas de comunicaciones móviles--Normas; comunicaciones aeronáuticas; modelado de canal; Ensanchamiento Doppler; LTE